Intergenerational Mobility of Immigrants in the Netherlands - Roel van Elk; Egbert L. W. Jongen; Patrick Koot; Alice Zulkarnain (Institute of Labor Economics (IZA), 2024)
A key measure of equality of opportunity is intergenerational mobility. Of particular interest is the extent to which children of immigrants catch up with natives. Using administrative data for the Netherlands, we find large gaps in the absolute income mobility of immigrants relative to natives (-23%), suggestive of large, persistent income gaps for future generations as well. Important drivers are differences in household composition and in personal incomes. However, we also uncover substantial heterogeneity by country of origin. Children of immigrants from China actually have higher incomes than natives, which is closely related to their educational outcomes.
Keywords: D31; J15; J61; J62; 330; intergenerational mobility; immigrants; Netherlands